SURFACE MODIFICATION OF CHEMICAL VAPOR DEPOSITION (CVD) DIAMOND FILM/SI(111) BY IMPLANTATION WITH Fe + B IONS IN CONJUNCTION WITH THEIR MAGNETIC PROPERTIES - Setyo Purwanto; A. Dimyati; R. Iskandar; Wisnu A.A; Tjipto S (GANENDRA Majalah IPTEK Nuklir, 2017)
Surface Modification of Chemical Vapor Deposition (CVD) Diamond Film/Si(111)  by Implantation with Fe+B ions In Conjunction with their  Magnetic Properties. Surfcace modification of CVD manufactured diamond films on Si(111) substrate has been performed by means of Fe+B ion implantation followed by Argon ion gas sputtering with acceleration energy 20 keV and ion dose 1x1015  and 1x1016 ions cm-2. Scanning Transmission Electron Microscope (STEM) imaging shows the formation of amorphous carbon layer on top of the diamond film with thickness ca. 100 nm on the implanted sample and ca. 20 nm on the sample without implantion. The morphology and magnetic property of the films surface were characterized by Atomic and Magnetic Force Microscopy (AFM/MFM). The Electron Energy Loss Spectroscopy EELS analysis has revealed amount of Boron atoms distributed homogenously inside the carbon amorphous layer on both samples which is in close agreement to the result of Raman Spectroscopy showing the changes of the Raman spectrum due to implantation. The magnetic properties of the samples after Fe+B ion implantion were additionally investigated by means of Vibrating Sample Magnetometer (VSM). By increasing ion doses at constant energy 20 keV, the magnetoresistance property decreased from +45% on the sample implanted with dose 1x1015 to +8% on the sample implanted with dose 1x1016 ions cm-2.